2009
DOI: 10.1097/aln.0b013e3181974fa2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure to Sevoflurane Induces Abnormal Social Behaviors and Deficits in Fear Conditioning in Mice

Abstract: This study shows that exposure of neonatal mice to inhaled sevoflurane could cause not only learning deficits but also abnormal social behaviors resembling autism spectrum disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
414
7
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(447 citation statements)
references
References 31 publications
23
414
7
3
Order By: Relevance
“…While others have used a range of 1–4% sevo on P7 rodents (Satomoto et al. 2009; Liang et al. 2010; Feng et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While others have used a range of 1–4% sevo on P7 rodents (Satomoto et al. 2009; Liang et al. 2010; Feng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Among these behaviors, social interaction impairment associated with neonatal sevo treatment has been reported previously by another group (Satomoto et al. 2009). Using a caged social target in an open field apparatus, the group demonstrated that the no‐sevo–treated control group interacted significantly more with the social target compared to the sevo‐treated group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several lines of evidence from animal models have suggested that excessive exposure to volatile anesthetics may cause irreversible and long-term behavioral changes resembling autism spectrum disorders (3). In clinical practice, sevoflurane is the most widely used inhaled anesthetics, particularly for cesarean section and surgical procedures in infants and young children (4,5); thus, the present study focused on sevoflurane.…”
Section: Introductionmentioning
confidence: 99%
“…There are some limitations to the present study. First, the concentration of sevoflurane was 1.9%, ing that rat pups exposed to anesthetics exhibit impaired acquisition of learned memory in adulthood (10,12,23). Here we find that the rats exposed to sevoflurane showed a high percentage of freezing in the contextual fear conditioning test during 4 min.…”
Section: Discussionmentioning
confidence: 63%
“…The first report shows that anesthetics administered to mice on postnatal day (PND) 7 increased neuronal apoptosis throughout the brain and induced working memory disorders in adulthood (10). A subsequent study found that 3% sevoflurane administered to mice at PND 6 for 6 h induced apoptosis in the hippocampus and prefrontal cortex and caused hippocampus-dependent and -independent neurocognitive deficits (23). The spurt of development of the rat nervous system during postnatal week (PNW) 2 corresponds to that between prenatal week 27 and 2 years after birth in humans (1,4,19,22).…”
mentioning
confidence: 99%